Human Rights Protection in Structural Corruption Through State Capture Practices by State and Non-State Actors - Riyandi, Riyandi; Wisnanto, Noer; Putra, Heri Suseno; Sukrisno, Wijayono Hadi; Thamrin, Husni (Jurnal Multidisiplin Indonesia, 2023)
The practice of state capture has become one of the most dangerous forms of structural corruption because it involves the control of state institutions by state and non-state actors for personal and group interests. This phenomenon creates distortions of the principle of the rule of law, undermines the democratic system, and directly violates human rights (HAM). In Indonesia, the involvement of political elites, bureaucracy, and economic oligarchs in the legislative process, public policy, and distribution of state resources has led to the weakening of institutions, marginalization of vulnerable groups, and obstruction of the fulfillment of human rights as guaranteed by the 1945 Constitution, Law No. 39 of 1999 concerning Human Rights, and international instruments such as the International Covenant on Civil and Political Rights (ICCPR). This study uses a normative juridical approach and conceptual analysis of state capture-based corruption by examining the inadequacy of existing regulations, particularly in the Corruption Crime Law. The results indicate that there is no explicit regulation regarding state capture as a criminal offense, as well as weak prevention mechanisms and systemic oversight of the infiltration of non-state actors into government structures. Therefore, legal reform is needed through the establishment of new norms, strengthening law enforcement and human rights institutions, and increasing public participation in the legislative process to protect human rights from the threat of structural corruption. These efforts are crucial steps in maintaining the rule of law and social justice in Indonesia.